1999
DOI: 10.1046/j.1471-4159.1999.0731660.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Peptide Methionine Sulfoxide Reductase in Alzheimer's Disease Brain

Abstract: Abstract:Previous studies have shown that the pathophysiology of Alzheimer's disease (AD) is linked to oxidative stress. Oxidative damage to different biomolecular components of the brain is a characteristic feature of AD. Recent evidence suggests that methionine may act as an antioxidant defense molecule in proteins by its ability to scavenge oxidants and, in the process, undergo oxidation to form methionine sulfoxide. The enzyme peptide, methionine sulfoxide reductase (MsrA), reverses methionine sulfoxide ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(165 citation statements)
references
References 41 publications
6
157
0
2
Order By: Relevance
“…3). Evidence supporting the possibility that MsrA may play an important role as an antioxidant in mammals comes from reports showing that reduction in MsrA activity occurs in very old rats (17) and in the brains of patients with Alzheimer's disease, which consequently leads to accumulation of carbonyl adducts in proteins (18). This phenomenon suggests that disruption of both MsrA and MsrB genes in mice should increase their vulnerability to oxidative stress even more.…”
Section: Discussionmentioning
confidence: 98%
“…3). Evidence supporting the possibility that MsrA may play an important role as an antioxidant in mammals comes from reports showing that reduction in MsrA activity occurs in very old rats (17) and in the brains of patients with Alzheimer's disease, which consequently leads to accumulation of carbonyl adducts in proteins (18). This phenomenon suggests that disruption of both MsrA and MsrB genes in mice should increase their vulnerability to oxidative stress even more.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with this hypothesis, we found that wildtype MsrA (but not two catalytically inactive mutants, C72S and C218S) protected dopaminergic neurons from two PD-related stresses: complex I inhibition and α-synuclein over-expression. Other groups have reported that MsrA is neuroprotective in vitro [21,50] and in vivo [25], and data from one study indicate that MsrA levels are decreased in the brains of Alzheimer's disease patients compared to age-matched controls [51]. A very recent study revealed that MsrA alleviates motor dysfunction and neurodegeneration in transgenic flies over-expressing α-synuclein [28].…”
Section: Discussionmentioning
confidence: 99%
“…In other reactions involving oxidation of the Met 35 formation of methionine sulfoxide (MetO) occurs, which can be reduced back to methionine by MetO reductase. The activity of MetO reductase is reduced in AD brain (161). AD brain, CSF, and plasma demonstrate increased levels of OS in AD (27,69,75,278).…”
Section: Application Of Redox Proteomics To Selected Neurodegenermentioning
confidence: 92%